Oligotomidae (Insecta: Embioptera) of Mt. Makiling, Los Baños, Philippines, with description of a new species - Lucañas, Cristian C.; Lit, Ireneo L. Jr. (Zootaxa, 2018)
The diversity of webspinners (Insecta: Embioptera) in Mt. Makiling, Los Baños was studied. Four species were recorded: Aposthonia borneensis (Hagen), A. merdelynae Lucañas & Lit n. sp., Oligotoma humbertiana (Saussure) and O. saundersii (Westwood). Each was illustrated and described. The new species differs from its congeners by relatively smaller size, subcylindrical left basal cercus with an inner lobe, and enlarged membranous area of the 10RP. A dichotomous key was devised to aid in identification of each species.